Running economy and gastrocnemius muscle length during running for kenyan and japanese elite distance runners - Enomoto, Y.; Suzuki, Y.; Okada, H.; Yokozawa, T. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to compare running economy and gastrocnemius muscle length during running for Kenyan and Japanese elite distance runners. Running economy was measured on the treadmill at 340 m/min while running motion was captured on the inside straight track at their racing speed. Gastrocnemius muscle length was estimated by the equation of Grieve et al. (1978) during the support phase at race speed running on the track. Kenyan runners showed higher running economy and smaller shortening length change of gastrocnemius during support phase than Japanese. These results suggest that shortening gastrocnemius during support phase of the running relates to running economy.